Nexus Between Possibility of Fraudulent Financial Reporting and Corporate Governance: Evidence from Bangladesh - Parvin, R.; Akter, M. (University of Jaffna, 2023)
This paper intends to test the nexus between the possibility of fraudulent financial reporting and the corporate governance in Bangladesh. The content analysis of annual reports has been performed for 125 Bangladeshi listed manufacturing companies. In this study, we apply more than one fraud indicator models such as Altman Z-score and Beneish M-score models to determine more accurately the chance of fraudulent financial reporting. The chance of fraudulent financial reporting is determined based on whether either one or both of Altman Z-score and Beneish Mscore models show red flags of potential fraud. This study found that board members with finance or accounting backgrounds are less likely to practice in misleading financial reporting since they may have the knowledge essential to understand fraudulent financial reporting strategies. This result implies that qualified directors may supervise financial reporting practices better, hence improving the quality of financial reports. Alternatively, some other components of corporate governance, such as board size, board independence, director ownership, gender diversity, and auditors' independence, have insignificant impacts on fraudulent financial reporting practices. This outcome indicates that these Bangladeshi corporate governance components may not be as strong in improving financial reporting credibility. In the context of Bangladesh, this is the first empirical study with management and policy implications. To the best of the writers’ knowledge, no article yet has been worked on the possibility of fraudulent financial reporting which calculated by multiple models and its relationship with the corporate governance in the context of Bangladesh.
Keywords: Altman Z-score Model; Beneish M-score Model; Corporate Governance; Earnings Management; Financial Statements; Fraudulent Financial Reporting; JEL Classcification: G34